DISTANCE EDUCATION AND METHODS OF ITS ORGANIZATION - Dusbekov Tuychi Mengnorovich (Galaxy International Interdisciplinary Research Journal, 2021)
The main purpose of the use of distance learning methods is the introduction of e-learning and the use of distance learning models LMS, MOODLE, OOOK in order to continue the learning process in education in the existing barriers to various processes.Development, wide application of information and communication and innovative technologies in the education system in international countries plays an important role in improving the quality of the education system. Organization of distance learning methods. Improving the quality of education by ensuring the implementation of relevant legal and regulatory documents,increasing the effectiveness of the use of information and communication technologies, Internet and multimedia resources in higher education is an urgent task today.